Climatic characteristics of the tropopause over the Arctic Basin - Nagurny, A. P. (CCSD, 1998)
International audience On the basis of stationary aerological observations and measurements at Russian "North Pole" drifting stations taken during 1954?1991, tropopause climate parameters (height and temperature at its upper and lower bounds) are determined. Long-term trends of these parameters over the Arctic Ocean are revealed.